2019
DOI: 10.1039/c9qi00942f
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the electronic structure of PtRu bimetallic nanoparticles for promoting the hydrogen oxidation reaction in alkaline media

Abstract: Alloying degree of PtRu bimetallic nanoparticles can be controlled to finely tune electronic effect for enhanced Hydrogen oxidation reaction in alkaline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 37 publications
1
30
0
Order By: Relevance
“…ydrogen fuel cell is considered as one of the most promising energy conversion devices due to its high energy efficiency and pollution-free feature [1][2][3][4][5] . Over the past decades, great efforts have been devoted to developing catalysts for hydrogen oxidation reaction (HOR) for enhancing the energy conversion efficiency of the hydrogen fuel cell 6,7 .…”
mentioning
confidence: 99%
“…ydrogen fuel cell is considered as one of the most promising energy conversion devices due to its high energy efficiency and pollution-free feature [1][2][3][4][5] . Over the past decades, great efforts have been devoted to developing catalysts for hydrogen oxidation reaction (HOR) for enhancing the energy conversion efficiency of the hydrogen fuel cell 6,7 .…”
mentioning
confidence: 99%
“…The Tafel curves derived from the polarization curves are shown in Fig. 7c, f ) indicated that FeP@PGL exhibited a faster kinetics in alkaline media [51][52][53].…”
Section: Orr Activities Of Catalysts In Acidic and Alkaline Mediamentioning
confidence: 93%
“…The binding energy of H ad on the Pt surface is relatively high, so the Volmer step usually restricts the HOR kinetics of most the Pt‐based nanocatalysts in the alkaline medium. [ 38 ] However, the evolution of the Tafel slope from the Pt/PC to Ru‐increased nanocatalyst suggests that the Ru‐increased nanostructure changes the rate‐determining step (RDS) of the Pt sites, possibly shifting from the Volmer to Tafel or Heyrovsky step. [ 17,39 ] The Ru‐based catalysts in the literature also have similar lower Tafel slope values (such as 43 mV dec –1 of Ru‐doped Pt/C [ 17 ] and ≈30 mV dec –1 of Ru x Pt y , [ 40 ] Table S1, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%